Effect of physicochemical parameters on the polygalacturonase of an Aspergillus sojae mutant using wheat bran, an agro‐industrial waste, via solid‐state fermentation. (4th January 2016) - Demir, Hande; Tari, Canan
Abstract: BACKGROUND: Polygalacturonases (PGs) are valuable enzymes of the food industry; therefore it is of great importance to discover new and GRAS PG‐producing microbial strains. In this study, PG enzyme produced from a high PG activity producer mutant Aspergillus sojae using wheat bran at the flask scale under pre‐optimized conditions of solid‐state fermentation (SSF) was biochemically characterized. RESULTS: The crude PG enzyme showed optimum activity in the pH range 4.0–5.0 and was stable in the pH range 3.0–7.0. The optimum temperature for the PG was 40 °C and it retained 99% of its activity at 50 °C. The mutant A. sojae PG could preserve more than 50% of its stability between 25 and 50 °C, both for 30 and 60 min, and was found to be stable in the presence of most of the tested compounds and metal ions. The inactivation energy ( E d ) was determined as 125.3 kJ mol −1 . The enthalpy (Δ H *), free energy (Δ G *) and entropy (Δ S *) of inactivation were found to be stable with increasing temperature. CONCLUSION: The mutant A. sojae PG could be suitable for the clarification (depectinization) of orange and grape juices and wine. © 2015 Society of Chemical Industry